The radical reflections of an applied economist - PHELPS BROWN, H. (PSL Quarterly Review, 2013)
The paper is a contribution to a series of recollections and reflections on the professional experiences of distinguished economists which the Banca Nazionale del Lavoro Quarterly Review started in 1979. In it Henry Phelps Brown looks back to reflect on the profession of economics. JEL: B31, A10